The Oxymoron of Carbon Dioxide Removal: Escaping Carbon Lock-In and yet Perpetuating the Fossil Status Quo? - Asayama, Shinichiro (Frontiers in Climate, 2021)
There appears to be a paradox in the debate over carbon dioxide removal (CDR) technologies. On the one hand, CDR is recognised as a crucial technical option to offset residual carbon emissions from fossil fuel use, so that it can help a transition to the net-zero energy system. But on the other hand, a serious concern is raised about CDR as a way to circumvent necessary emissions reduction, hence perpetuating the status quo of fossil fuel use. This apparent paradox of CDR, however, has less to do with technology itself but more with the difficulty to move away from carbon lock-in—the deeply entrenched fossil-fuel-based energy system. The challenge of decarbonisation is indeed about eroding the deep lock-ins that perpetuate the production and consumption of fossil fuels. To understand the role of CDR in overcoming carbon lock-in, looking back the past debate on carbon capture and storage (CCS) is instructive. Although both CCS and CDR are criticised for keeping the fossil status quo, there is a crucial difference between them. Unlike CCS, CDR can possibly avoid the risk of reinforced lock-in, given its physical decoupling from fossil fuel use. And yet CDR has the risk of undue substitution that continues unjustly fossil carbon emissions. A change of the framing question is thus needed to puzzle out the paradox of CDR. To rightly place CDR in the challenge of rapid decarbonisation, we should ask more how CDR technologies can be used in alignment with a managed decline to fossil fuel production.